2018
DOI: 10.32861/jssr.spi6.1225.1230
|View full text |Cite
|
Sign up to set email alerts
|

Effect of 4-Weeks Traditional Archery Intervention on Hand-Eye Coordination and Upper Limb Reaction Time Among Sedentary Youth

Abstract: This studyaims to determine the effect of a 4-weeks traditional archery intervention on hand-eye coordination and upper limb reaction time in sedentary youth. Methods: Thirty sedentary youth with leisure time activities of less than 150 minutes/week (mean age = 21.03 ± 1.61 years old) were randomly assigned into an intervention and a control group. A specific regimen of traditional archery training was given to the intervention group for 4 weeks, the control group on the other hand was requested to maintainthe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…In a study aiming to determine the effect of traditional archery training on hand-eye coordination and upper extremity reaction time, the reaction time of the experimental group was higher than the control group. Still, the intervention effect was not statistically significant (Zolkafi et al, 2018). A comparable study investigating the reaction time of bocce athletes has not been found in the literature.…”
Section: Discussionmentioning
confidence: 66%
See 1 more Smart Citation
“…In a study aiming to determine the effect of traditional archery training on hand-eye coordination and upper extremity reaction time, the reaction time of the experimental group was higher than the control group. Still, the intervention effect was not statistically significant (Zolkafi et al, 2018). A comparable study investigating the reaction time of bocce athletes has not been found in the literature.…”
Section: Discussionmentioning
confidence: 66%
“…In this study, which aimed to compare the reaction times of athletes who participated in archery and bocce training for at least two years, no statistically significant difference was observed between bocce petanque athletes and Olympic archers in terms of reaction time (p>.05). Since target shooting sports are static branches that require high control in movement, reaction time is an important factor that increases performance in such sports (Zolkafi et al, 2018). This is the first study in the literature to compare bocce and archery branches in terms of reaction time.…”
Section: Discussionmentioning
confidence: 99%